ANALISIS PENGARUH RASIO KEUANGAN TERHADAP NILAI PERUSAHAAN - Ika Listyawati; Rosiana Ramadhan (MAKSIMUM, 2017)
The purpose of this study was to test and analyze the influence of financial ratios on firm value carriedout in the manufacturing companies listed on the Indonesia Stock Exchange period 2013 to 2017. The samplingin this study used a purposive sampling technique. Based on predetermined criteria, this study uses multiplelinear regression analysis with the help of the SPSS program. The results of multiple linear regression analysis were obtained by the regression equation Y = α +β1x1 + β2x2 + β3x3 + ε. Based on the results of hypothesis testing, it was found that the variables of profitabilityand capital structure had a positive and significant effect on the value of the company, while the variablegrowth of the company was not significant towards firm value.